Examining EFL Students' Experiences in Developing Instructional Multimedia for Technology Integration in Educational Courses - Rehuwella Lestary Ipung; Ventje Jany Kalukar; Effendi Limbong (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
This study aimed: (1) to elaborate EFL students’ experiences in developing instructional multimedia on technology in education course; (2) to elaborate the difficulties and the solutions EFL students face in developing instructional multimedia on technology in education course. This study used a case study qualitative research design. The participants of this study were four students of English Education Department at Mulawarman University who were selected with specific criteria. Interview and documentation were used as instruments for this study.The result showed that most of the students in the Technology in Education course had applied their knowledge in creating content in their experience in developing instructional multimedia. The result also showed Based on the results, the difficulties that were found came from content of the material technology, video, managing time, and design.